2016
DOI: 10.1007/s11250-016-1212-5
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence profile of enterococci isolated from poultry and cattle sources in Nigeria

Abstract: This study investigated the occurrence, antimicrobial resistance and virulence of Enterococcus from poultry and cattle farms. Three hundred and ninety samples: cloacal/rectal swabs (n = 260) and manure (n = 130] were processed for recovery of Enterococcus species. Standard bacteriological methods were used to isolate, identify and characterize Enterococcus species for antimicrobial susceptibility and expression of virulence traits. Detection of antibiotic resistance and virulence genes was carried out by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 58 publications
3
26
1
Order By: Relevance
“…Enterococci have emerged as a major public health concern, especially vancomycin resistant E. faecalis and E. faecium which are more difficult to treat (43). Of the 176 isolates screened for antimicrobial resistance, all were susceptible to vancomycin, a result that agrees with previous studies that have suggested that cattle feces are not a major source of vancomycin-resistant enterococci (16,44). In the present study, resistance to tylosin, erythromycin and doxycycline was most prevalent among isolated enterococci.…”
Section: Discussionsupporting
confidence: 91%
“…Enterococci have emerged as a major public health concern, especially vancomycin resistant E. faecalis and E. faecium which are more difficult to treat (43). Of the 176 isolates screened for antimicrobial resistance, all were susceptible to vancomycin, a result that agrees with previous studies that have suggested that cattle feces are not a major source of vancomycin-resistant enterococci (16,44). In the present study, resistance to tylosin, erythromycin and doxycycline was most prevalent among isolated enterococci.…”
Section: Discussionsupporting
confidence: 91%
“…This category included 42 studies, with the inclusive eligibility criteria in which diverse phenotypic or genotypic methods were utilized ([14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], Tables S1–S3). These studies sought to detect the presence and extent of AMR in collected samples with a selected panel of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The 80 studies excluded did not directly relate to the objectives or yielded information that could be subjected to organized peer review and data analysis. The 59 included studies were sorted into three categories of 42 antimicrobial resistance studies [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], 16 antimicrobial residue studies [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], and 1 antiseptic or disinfectants study [72]. The PRISMA-style flowchart was modified and used for this analytical review (Figure S1) [73].…”
Section: Methodsmentioning
confidence: 99%
“…Osman et al [47] 2019 Egypt Poultry Culture& Kateete et al [48] 2019 Uganda Clinical specimen Culture Frank et al [49] 2019 South Africa Feaces, water & soil Culture& shows that the subgroup analysis of VRE at country level Figure 3 shows the subgroup analysis based on the source of the sample for VRE in Africa…”
Section: Resultsmentioning
confidence: 99%
“…Whatever the sample type and laboratory method employed captured for the review and meta-analysis. The author name, year of publication, country of origin, source of sample (human vs non-human), laboratory method used Tanzania [40][41][42] and Uganda, [43][44][45]), two (2) articles from Nigeria, [46,47] and one (1) article from Algeria [48] were included for the review as presented in Table 1.…”
Section: Study Featuresmentioning
confidence: 99%